Constraining inflationary scalar field models with CMB spectral distortions - Leskinen, Juuso (2020)
The Cosmic Microwave Background (CMB) demonstrates extreme uniformity, with only small temperature anisotropies of the order of 10^(-5). These anisotropies are believed to originate from primordial density perturbations, caused by quantum fluctuations of scalar fields during the cosmic inflation. In the canonical scenario, the single-field slow-roll inflation, these perturbations are assumed to be sourced by one field, the inflaton. However, it is possible that there are multiple fields present during inflation, that give contribution to the perturbations.